Addressing barriers to exclusive breast-feeding in low- and middle-income countries: a systematic review and programmatic implications. Issue 17 (2nd October 2017) - Kavle, Justine A; LaCroix, Elizabeth; Dau, Hallie; Engmann, Cyril
Abstract: Objective: Despite numerous global initiatives on breast-feeding, trend data show exclusive breast-feeding (EBF) rates have stagnated over the last two decades. The purpose of the present systematic review was to determine barriers to exclusive breast-feeding in twenty-five low- and middle-income countries and discuss implications for programmes. Design: A search of Scopus, MEDLINE, CINAHL and PsychINFO was conducted to retrieve studies from January 2000 to October 2015. Using inclusion criteria, we selected both qualitative and quantitative studies that described barriers to EBF. Setting: Low- and middle-income countries. Subjects: Following application of systematic review criteria, forty-eight articles from fourteen countries were included in the review. Results: Sixteen barriers to EBF were identified in the review. There is moderate evidence of a negative association between maternal employment and EBF practices. Studies that examined EBF barriers at childbirth and the initial 24 h post-delivery found strong evidence that caesarean section can impede EBF. There is moderate evidence for early initiation of breast-feeding and likelihood of practising EBF. Breast-feeding problems were commonly reported from cross-sectional or observational studies. Counselling on EBF and the presence of family and/or community support have demonstrated improvements in EBF. Conclusions: Improving the counselling skills of health workers to address breast-feeding problems and increasing community support for breast-feeding are critical components of infant and young child feeding programming, which will aid in attaining the 2025 World Health Assembly EBF targets. Legislation and regulations on marketing of breast-milk substitutes, paid maternity leave and breast-feeding breaks for working mothers require attention in low- and middle-income countries.